Pemanfaatan Literasi Digital Dalam Rumpun PAI - Ikhlasul Amalia, Riza; pengelola, pengelola (STAI Ihyaul Ulum Gresik, 2024)
This study aims to describe the Utilization of Digital Literacy in PAI Learning at Man 2 Banyumas. This research is a qualitative research, data obtained through observation, interviews, and documentation. Data were processed through data reduction, data presentation and data verification. Data validity is done through triangulation techniques. The results of the research obtained from the description of the utilization of digital literacy in PAI learning at Man 2 Banyumas are as follows: in the utilization of digital literacy in PAI learning, there are forms of learning activities by utilizing digital literacy, namely the use of computers during learning, the use of laptops during learning, accessing wifi, and accessing the internet. In using computers and laptops, teachers direct students to access learning-related materials such as in Ushul Jurisprudence and Aqidah Akhlak, teachers give directions to find other accurate learning resources and teachers direct students to watch educational videos related to learning through Youtube. By utilizing the use of computers and laptops, of course, teachers need wifi and internet access to support the use of computers and laptops. The teacher also allows access but remains under teacher supervision so that students do not abuse the use of computers, laptops wifi and internet. This is the core of PAI learning that teachers usually do in every learning activity. . Therefore, educators must also increase their knowledge in operating various digital media so that during the learning process can take place pleasantly and can be easily understood. If it is easy to understand, it will certainly give positive results to the students.